SISTEM INFORMASI GEOGRAFIS MUSHOLLAH(TPQ) LEGALITAS KEMENAGKABUPATEN SITUBONDO BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL - Helmi, Fauzi; Dharmawan, Johan (Journal of Advanced Research in Informatics, 2023)
Geographic Information System (GIS) is a computer-based system used to store and manipulate geographic information. GIS is designed to collect, store, and analyze objects and phenomena in which geographical location is an important or critical characteristic to be analyzed. Regarding the location of Musollah (TPQ), the people of Kabupaten Situbondo do not know much about its distribution. So in need of a system to map Musollah (TPQ). This study focuses on Musollah mapping (TPQ) supported by information about Musollah (TPQ). This GIS build uses data collection methods by collecting data in the Musollah Section of the Ministry of Religious Affairs Office of Situbondo Regency with a sample of several Musollah (TPQ), Waterfall system development method and Data Flow Diagram (DFD) for its system design. The tool used to build the GIS is to use the Google Maps API as a base map to show Situbondo County area, PHP as a web programming language, and to use MySQL as its database. The output of this system is the dispersion map of Musollah (TPQ) in Situbondo based on its coordinate location with supporting information which includes the address of Musollah (TPQ), Caregiver, and the number of santri and the existing facilities in Musollah (TPQ).